How architecture got its hump - Connah, Roger (Preston Thomas memorial series in architecture., 2001)
"In How Architecture Got Its Hump, Roger Connah explores the "interference" of other disciplines with and within contemporary architecture. He asks whether photography, film, drawing, philosophy, and language are merely fashionable props for architectural hallucinations or alibis for revisions of history. Or are they a means for widening the site of architecture? Connah shows how these disciplines have not only contributed to new developments in architectural theory and practice, but also have begun to insinuate new possibilities of space.